2019
DOI: 10.1108/md-10-2018-1084
|View full text |Cite
|
Sign up to set email alerts
|

Diving into emerging economies bottleneck: Industry 4.0 and implications for circular economy

Abstract: Purpose In this paper, the authors aim to explore the relationship between the concepts of Industry 4.0 and circular economy (CE) as a contribution to the management decision on emerging countries. By analyzing the trends of scientific production to ascertain the interface of both constructs, the purpose of this paper is to identify limitations for Industry 4.0 and CE implementation in Brazil, as well to present an original framework and strategic pathways to overcome limitations for emerging countries. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 56 publications
2
80
0
1
Order By: Relevance
“…Efficiency and energy saving of manufacturing processes can be improved by technology adoption ( Nascimento et al., 2018 ). Make to specifications, efficient energy usage, tractability, and closed-loop SCM can be managed by application of Industry 4.0 technologies ( Cezarino et al., 2019 ). Fundamentals of the closed supply chain (circular economy) have introduced a new approach to sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Efficiency and energy saving of manufacturing processes can be improved by technology adoption ( Nascimento et al., 2018 ). Make to specifications, efficient energy usage, tractability, and closed-loop SCM can be managed by application of Industry 4.0 technologies ( Cezarino et al., 2019 ). Fundamentals of the closed supply chain (circular economy) have introduced a new approach to sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Chauhan et al. (2019) and Cezarino et al. (2019) have observed that with the association of Industry 4.0, manufacturing operations may become sustainable and ethical.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Adoption of Industry 4.0 leverages the value chain of businesses that enhances the connectivity and horizontal & vertical integration of businesses and transforming into smart factories with the help of the Cyber-Physical System (Hazen, Skipper, Ezell, & Boone, 2016;Trade, 2014). The profound advancement of digital technologies embedded with higher-level manufacturing process automatically administered by cognitive information systems in smart factories in the form of intelligent sourcing, self-optimization, and self-customization (Cezarino, Liboni, Stefanelli, Oliveira, & Stocco, 2019;Hazen et al, 2016;Stankovic et al, 2017). The invention of flexible automation systems help to produce customized goods and services according to the preferences and needs of different customers with a higher degree of efficiency in large quantities (Accorsi, Bortolini, Baruffaldi, Pilati, & Ferrari, 2017;Gokalp, Kayabay, Akyol, Eren, & Koçyiğit, 2016;Huckle, Bhattacharya, White, & Beloff, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly pervasive in manufacturing is industry 4.0 adoption [8,34,48]. Industry 4.0 is the synonym for the transformation of today's factories into smart factories.…”
Section: Challenges In Smart Remanufacturing Operations: a Simulationmentioning
confidence: 99%